Penerapan Metode Design Thinghking Dalam Perancangan Aplikasi Mobile Atap Class Dengan Tools Figma - Audia (Universitas Lampung, 2025)
Atap Class is a learning space and facility designed to share insights and knowledge, especially for vocational high school students and interns. In today's digital era, developing effective and user-friendly mobile applications is essential to improve user experience. This study aims to apply the Design Thinking method in developing the UI/UX of the Atap Class mobile application. By using Figma tools, the design process will be carried out iteratively, starting from the empathy, definition, ideation, prototyping, to testing stages. The results of this study are expected to produce applications that not only meet user needs but also increase user interaction and satisfaction with the Atap Class platform.